In vivo human head MRI at 10.5T: A radiofrequency safety study and preliminary imaging results - Sadeghi‐Tarakameh, Alireza; DelaBarre, Lance; Lagore, Russell L.; Torrado‐Carvajal, Angel; Wu, Xiaoping; Grant, Andrea; Adriany, Gregor; Metzger, Gregory J.; Van de Moortele, Pierre‐Francois; Ugurbil, Kamil; Atalar, Ergin; Eryaman, Yigitcan (Magnetic resonance in medicine, 2020)
Purpose The purpose of this study is to safely acquire the first human head images at 10.5T. Methods To ensure safety of subjects, we validated the electromagnetic simulation model of our coil. We obtained quantitative agreement between simulated and experimental B1+ and specific absorption rate (SAR). Using the validated coil model, we calculated radiofrequency power levels to safely image human subjects. We conducted all experiments and imaging sessions in a controlled radiofrequency safety lab and the whole‐body 10.5T scanner in the Center for Magnetic Resonance Research. Results Quantitative agreement between the simulated and experimental results was obtained including S‐parameters, B1+ maps, and SAR. We calculated peak 10 g average SAR using 4 different realistic human body models for a quadrature excitation and demonstrated that the peak 10 g SAR variation between subjects was less than 30%. We calculated safe power limits based on this set and used those limits to acquire T2‐ and T2∗‐weighted images of human subjects at 10.5T. Conclusions In this study, we acquired the first in vivo human head images at 10.5T using an 8‐channel transmit/receive coil. We implemented and expanded a previously proposed workflow to validate the electromagnetic simulation model of the 8‐channel transmit/receive coil. Using the validated coil model, we calculated radiofrequency power levels to safely image human subjects.